2019
DOI: 10.3390/microorganisms7070197
|View full text |Cite
|
Sign up to set email alerts
|

Winning the War against Multi-Drug Resistant Diarrhoeagenic Bacteria

Abstract: Drug-resistant-diarrhoeagenic bacteria are currently emerging healthcare challenge. This study investigated the effects of Vernonia amygdalina, Garcinia kola, tetracycline and metronidazole combinations on such bacteria. Agar well diffusion method was employed to determine the inhibitory effects of the herbal extracts on diarrhoeagenic bacteria while Time-Kill Assay was used to determine bactericidal effects of the extracts against test isolates. Interactions between plant extracts and antibiotics were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…For instance, the triple antibiotic paste (containing equal amounts of minocycline, ciprofloxacin, and metronidazole) is very effective in eliminating wide range of bacteria causing teeth decay [35]. Combination of tetracycline and metronidazole was found to be effective against multi-drug resistant diarrhoegenic bacteria [36].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the triple antibiotic paste (containing equal amounts of minocycline, ciprofloxacin, and metronidazole) is very effective in eliminating wide range of bacteria causing teeth decay [35]. Combination of tetracycline and metronidazole was found to be effective against multi-drug resistant diarrhoegenic bacteria [36].…”
Section: Discussionmentioning
confidence: 99%
“…In other natural matrixes, Enemchukwu et al (2019) studied Vernonia amygdalina, Garcinia kola, tetracycline and metronidazole and combinations and found that synergic activity exists against diarrheagenic bacteria. Mancarz et al ( 2019) studied a synergic interaction of two extracts from Liquidambar styraciflua with ciprofloxacin and tetracycline and a synergistic interaction was observed against the gram-positive bacterial Enterococcus faecalis (ATCC 29212) and S. aureus (ATCC 2592).…”
Section: Discussionmentioning
confidence: 99%
“…The search for plant based antifungal agents to tackle this menace has been on the increase probably due to their recorded improved effects over conventional antifungal agents [4,5]. Factors such as side effects, emergence of resistant strains, costs and availability have hindered wide utilization of some conventional antimicrobial drugs [6,7]. More so, bio-prospecting of medicinal plants as a reliable alternative for new drug candidates over the years has proven to be a reliable source of surplus biologically active molecules [8,9].…”
Section: Introductionmentioning
confidence: 99%